2015
DOI: 10.7717/peerj.829
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a research field—a micro (RNA) example

Abstract: Background. Every new scientific field can be traced back to a single, seminal publication. Therefore, a bibliometric analysis can yield significant insights into the history and potential future of a research field. This year marks 21 years since that first ground-breaking microRNA (miRNA) publication. Here, we make the case that the miRNA field is mature, utilising bibliometrics.Methods. Utilising the Web of Science™ (WoS) database publication and citation information, we charted the history of miRNA-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…The intrinsically high stability of miRNAs in bio-fluids together with, in some cases [11], their tissue-specificity, confers miRNAs a significant potential as non-invasive biomarkers of disease [1214]. So far, a plethora of studies have shown the association between specific plasma and serum miRNA signatures and human cancer, heart disease and autoimmune diseases (reviewed in [15, 16]), as well as, in a reproductive context, pregnancy progression and preeclampsia [1719].…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsically high stability of miRNAs in bio-fluids together with, in some cases [11], their tissue-specificity, confers miRNAs a significant potential as non-invasive biomarkers of disease [1214]. So far, a plethora of studies have shown the association between specific plasma and serum miRNA signatures and human cancer, heart disease and autoimmune diseases (reviewed in [15, 16]), as well as, in a reproductive context, pregnancy progression and preeclampsia [1719].…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are small (19–22 nucleotides) non‐coding RNAs that regulate gene expression. First described by Lee and colleagues in 1993, research into miRNAs has grown exponentially in recent years as the role of miRNA in cancer biology is defined. In general, miRNA genes are transcribed in the nucleus by RNA polymerase II .…”
Section: Micro‐rnasmentioning
confidence: 99%
“…Since their discovery in 1993, knowledge of the role of miRNAs in regulating gene expression across a spectrum of pathological processes has grown exponentially . It is now recognized that certain miRNAs are highly specific for tissue and developmental stages, exerting a regulatory effect on a myriad of cellular processes including cell development, differentiation, proliferation and apoptosis .…”
Section: Micro‐rnasmentioning
confidence: 99%
“…13,14 Since their discovery in 1993, knowledge of the role of miR-NAs in regulating gene expression across a spectrum of pathological processes has grown exponentially. 15 It is now recognized that certain miRNAs are highly specific for tissue and developmental stages, exerting a regulatory effect on a myriad of cellular processes including cell development, differentiation, proliferation and apoptosis. 12,14,16 Many miRNA are expressed in tissueand disease-specific patterns and are known to correlate with clinicopathological features and prognostic indices across a spectrum of pathologies.…”
Section: Micro-rnasmentioning
confidence: 99%